Hukum Meratapi Mayit Menurut Ḥadīṡ Riwayat Al-Bukhārī Nomor 1226: Kajian Ma’ān Al-Hadis - Sulis, Sulis; Damanik, Nurliana; Munandar, Munandar (AHKAM, 2024)
Death is either the opposite of life or its absence. One of Allah's unexpected wills is death. Rasūlullāh Ṛaw's instructions on how to care for a corpse are the best sources of advice and direction. The Prophet Ṣaw gave guidance, namely on how family members and other relatives should handle the deceased. In order for living people to take care of the body after someone has passed away, some things need to be done right away. Nevertheless, there are several exceptions made by Muslims to the proper ways to handle corpses, meaning that a significant portion of Muslims are ignorant of the protocol in dealing with corpses in accordance with the teachings of Rasūlullāh Ṣaw. This research aims to find out how ḥadīṡ about mourning the dead in the history of al-Bukhārī number 1226, the perspective of ma'ān al-Ḥadīṡ and its understanding. This type of research is qualitative research. In understanding ḥadīṡ, several approaches are used, including linguistic, anthropological and socio-historical approaches. The result that the author found was that mourning for the dead in Islam is not permitted. If you are just crying as a natural expression of sadness, don't scratch your face, tear your clothes, pull your hair and loudly wail because Rasūlullāh Ṣaw never exemplified this. The corpse that is tortured in the ḥadīṡ is if during his lifetime he made a will to his family so that when he died the family would mourn his passing, whereas if he did not make a will during his lifetime, he would not be tortured because of his family's cries as intended in the ḥadīṡ.